Viaggiare in compagnia: approdi, insediamenti e ripartenze della Life course research tra Stati Uniti e Europa - Manuela Olagnero (Cambio, 2025)
The aim of these pages is to give an account of how Life Course Research (henceforth LCR), which originated in the 1970s in the United States, took root in Europe in the 1980s-1990s. It does so thanks to a program combining innovation and fidelity to the classics, interdisciplinary openness, grafting onto already sensitive terrain in the target countries, and methodological proposals that many different actors, included policy makers, use across a broad spectrum of themes and problems. In the following years the LCR gained visibility by accrediting itself as a paradigm of reference for the analysis of the relationship between life courses and welfare systems in Europe. Always self-critical about the milestones missed by the research, life course scholars recently discuss its theoretical framework opening also to other sociological paradigms, e.g. that of social networks. The scientific reputation of LCR is also fuelled by an endless work of enlarging “umbrella” of longitudinal analysis among different audiences.